Perbandingan Metode SAW, WP, Dan TOPSIS Dalam Pemilihan Wedding Organizer Di Surabaya - Siti Jukhoriyah; Maulana Bintang Setiawan; Raka Galih Pramuja; Himawan Darmaji; Perani Rosyani (CV. Multi Kreasi Media, 2023)
Currently, there are many Wedding Organizer (WO) services that make it easier for the bride and groom to prepare for the wedding. Each WO service offers a large selection of attractive, competitive and specific wedding service packages. On the other hand, this sometimes makes it difficult for the bride and groom to choose a WO. To assist in determining decision making, a Decision Support System (DSS) approach is used. The criteria used include: rating, year of establishment, price, photo per roll, variety of food menus. This study aims to analyze the results of the Simple Additive Weighting (SAW), Weighted Product (WP) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) methods so that it can be determined which method is more relevant to apply. in terms of WO election in Surabaya. This research will discuss the process of determining the Wedding Organizer (WO) by analyzing three methods, namely the Simple Additive Weighting (SAW) method, the Weighted Product (WP) method and the Technique for Order of Preference by Similarity to Ideal Solutions (TOPSIS method). Although in general the three methods are relatively equally relevant.